(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
This paper presents a fictile truncated pyramid-shaped artifact found during the excavations and research of the University of Milan at the ’monumental complex’ of Tarquinia. It was found in a structure excavated in the bedrock during the Villanovan period in the H-M Sector, an unpublished context still under study. Not being able to place this finding in any of the classes of materials usually found due to its strong fragmentation, this contribution aims to present a preliminary report of the literary review and explore similarities and differences within the archaeological record from the formal and functional point of view.